If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3k + 7 = 5k + -1k Reorder the terms: 7 + -3k = 5k + -1k Combine like terms: 5k + -1k = 4k 7 + -3k = 4k Solving 7 + -3k = 4k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-4k' to each side of the equation. 7 + -3k + -4k = 4k + -4k Combine like terms: -3k + -4k = -7k 7 + -7k = 4k + -4k Combine like terms: 4k + -4k = 0 7 + -7k = 0 Add '-7' to each side of the equation. 7 + -7 + -7k = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -7k = 0 + -7 -7k = 0 + -7 Combine like terms: 0 + -7 = -7 -7k = -7 Divide each side by '-7'. k = 1 Simplifying k = 1
| -2x+1=-5x-4 | | (1-1/x^2)(y-1) | | R^2-16r-55=-6 | | 4q-8=2(2q+7) | | 49-19=5(x-6) | | R^2-16r-49=0 | | 3h+2f+z=20 | | 72-g+36= | | v^2+7v+5=-7 | | 21+5y-1=17y-12-4y | | -6-3+3x-1=4x-5 | | 7x+32=13x-12 | | -(1/2)=-4x^-3 | | -.5x^2+25x-105=0 | | (x+4)+(-2x-6)= | | 90+31+b=180 | | 6h-(2-4h)=4(2h-3) | | -43=6(b-4) | | 4x+88=14x+8 | | 24.4+2.7x=5x-39.8 | | 30x^2+3x-9=0 | | 9x+24=6x-24 | | 6ln(4)-6ln(1)= | | (5x+4)+(7x+1)= | | -2(1-3n)+3=1+6n | | -24-2m=-2m-4(5m+1) | | 11i-(4+7i)= | | 6(x+5)+3=2(x+4)+4(x+7)-3 | | (-3x-4)-(3x+3)= | | (X+3)6=(2x-1)3 | | (x-3)=4x-9 | | -5+9=-4x-3 |